Comparative Analysis Of Russian And Foreign Territorial Brands - Mojshevich Eidelman, Boris; Kazan Federal University, Institute of Management, Economics and Finance (2017)
The article provides a comparative analysis of territorial brands development and promotion both in the Russian Federation and abroad on the level of countries, provinces and cities. The authors consider foreign territorial brands of such states, as Australia and Germany, the Austrian Land Tyrol and the Chinese city of Hong Kong, showing their strengths and opportunities for promoting the respective territorial entities. Russian territorial brands under discussion include Saint Petersburg, Omsk and Kaluga regions, Perm, Ulyanovsk and Kazan.Much attention is paid to comparing the strengths and weaknesses of domestic and foreign territorial brands. In the conclusion the authors state that every region of the Russian Federation should create its own original brand, which should complement and develop each other. The researchers emphasize the necessity of creating a national Russian brand